A wearable activity tracker intervention for promoting physical activity in adolescents with juvenile idiopathic arthritis: a pilot study - Liane D. Heale; Saunya Dover; Y. Ingrid Goh; Victoria A. Maksymiuk; Greg D. Wells; Brian M. Feldman (BMC, 2018)
Abstract Background Children and adolescents with juvenile idiopathic arthritis (JIA) are less physically active than their healthy peers and are at high risk of missing out on the general health benefits of physical activity. Wearable activity trackers are a promising option for intervening in this population with potential advantages over traditional exercise prescriptions. The objectives of this study were to: (1) determine the feasibility of a wearable activity tracker intervention in adolescents with JIA; and (2) estimate the variability in response to a wearable activity tracker intervention on the physical activity levels of adolescents with JIA. Methods Participants aged 12-18 years with JIA were recruited during their routine rheumatology clinic visits at a tertiary care hospital. Participants completed the 3-Day Physical Activity Recall self-reported questionnaire at baseline, 1 week and 5 week follow-up. At the 1 week follow up, participants were instructed to start wearing an activity tracker for 28 consecutive days. Participants completed a feasibility questionnaire at their end of study visit. Participant demographics, adherence rates and feasibility outcomes were summarized using descriptive statistics. The effect of wearing a tracker on moderate-to-vigorous physical activity (MVPA) and total metabolic equivalents (METs) per day were analyzed using a paired t-test. Results Twenty-eight participants (74% female; median age 15.1, range 12.8-18.6) were included in the analysis. All of the participants were able to synchronize the activity tracker to a supported device, use the activity tracker correctly and complete the study measurements. On average, participants had activity logged on their smartphone application for 72% of the intervention period. The standard deviation of the change in mean METs/day was 12.148 and for mean MVPA blocks/day was 3.143 over the study period. Conclusion Wrist worn activity tracking is a feasible intervention for adolescent patients with JIA. More research is needed to examine the effect of activity tracking on physical activity levels. Trial Registration Not an applicable clinical device trial as per the criteria listed on ClinicalTrials.gov as the primary objective is feasibility.